Performance Analysis of TAS and RAS with CPM Modulation in Two-way Relaying MIMO Systems - Guowei, Lei; Yuanan, Liu (Wireless personal communications, 2021)
Up to now, considerable results have been concluded for two-way relaying system with linear modulations. The performance of both transmit antenna selection (TAS) and receive antenna selection (RAS) needs to be investigated in some two-way relaying multiple-input multiple-output (TWRM) systems. In this paper, the goal is to investigate the nonlinear modulations, i.e. , continuous phase modulation (CPM) in TWRM systems. Firstly, it is urgent to decrease the decoding complexity of the phase states subject to various modulation index of CPM. Then, the performances of both TAS and RAS with CPM modulations in TWRM systems are analyzed and evaluated. More exactly, the pair wise probability (PEP) is used to evaluate the performance based on analysis of CPM signal matrix, which is computed in a new form of the Laurent expression. Further, the tight upper-bounds for the frame error rate (FER) are derived for CPM in TWRM systems. Finally, simulations show in good agreement with the analysis in this paper.